2016
DOI: 10.1042/bsr20160187
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in low back pain may be detected from the peripheral blood: suggestions for biomarker

Abstract: The results of our study provides novel insights into the mechanisms of low back pain, as well as provide suggestions of the possibility that these assays may be used as biomarkers for low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 12 publications
5
41
1
2
Order By: Relevance
“…Circulating inflammatory markers have been found in such patients [46] and it may be hypothesised that the greater the unevenness of motion sharing, the greater the likely prevalence of rapid displacements during physical tasks causing the release of cytokines from failing holding elements.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating inflammatory markers have been found in such patients [46] and it may be hypothesised that the greater the unevenness of motion sharing, the greater the likely prevalence of rapid displacements during physical tasks causing the release of cytokines from failing holding elements.…”
Section: Discussionmentioning
confidence: 99%
“…[4749] Cytokines can be divided into proinflammatory and anti-inflammatory cytokines, and many different cytokines have been investigated in FMS (Rodiguez-Pinto et al). [25] Increased serum levels of IL-6 and IL-8 have been reported in several studies of FMS.…”
Section: Discussionmentioning
confidence: 99%
“…Human and preclinical model studies have observed a possible correlation between the back pain of intervertebral disc degeneration and pro‐/anti‐inflammatory mediators in different bio‐fluids (CSF/blood) .…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating clinical and experimental evidence confirming the existence of potent, adaptive interactions between the central and peripheral aspects of the Neuro‐immune System in the genesis and maintenance of chronic neuropathic and nociceptive back pain . The neuro‐inflammatory pathway is modulated by the interaction of pro‐ and anti‐inflammatory cytokines and chemokines, and peripheral immune system‐derived cells (macrophages, leukocytes).…”
Section: Introductionmentioning
confidence: 99%